The complete letters of Henry James, 1880-1883. - James, Henry (University of Nebraska Press, 2017)
The Complete Letter of Henry James, 1880-1883, volume 2, contains 178 letters, of which 98 are published for the first time.
Keywords: James, Henry, -- 1843-1916 -- Correspondence.; James, Henry, -- 1843-1916; Authors, American -- 19th century -- Correspondence.; Authors, American -- 20th century -- Correspondence.; Écrivains américains -- 19e siècle -- Correspondance.; Écrivains américains -- 20e siècle -- Correspondance.; LITERARY COLLECTIONS -- Letters.; Authors, American; 1800-1999; Personal correspondence